Wegener’s Granulomatosis: Extraosseous Uptake in HDP Bone Scintigraphy- A Case Report (Bangladesh Journal of Nuclear Medicine, 2017)
Bone scan is most frequently prescribed for evaluation of patients with known malignancy or screening of bony uptake for unexplained body ache. Extraosseous uptake in bone scan is point of interest because sometimes additional information could be found beside skeletal abnormality. Here we discuss an interesting case of extraosseous uptake.Bangladesh J. Nuclear Med. 18(1): 61-63, January 2015